Lipid droplet distribution of immature canine oocytes in relation to their size and the reproductive stage. (30th September 2015) - Ariu, Federica; Strina, Alessandro; Murrone, Ombretta; Falchi, Laura; Bebbere, Daniela; Ledda, Sergio; Zedda, Maria Teresa; Pau, Salvatore; Bogliolo, Luisa
Abstract: This study investigated the distribution of lipid droplets (LD) in immature canine oocytes in relation to their size and the reproductive stage. Oocytes were collected from the ovaries of bitches at different estrous stages, divided according to their size (110‐120 µm; >120 µm), and stained with Nile Red to detect lipid droplet distribution. At the follicular phase most of the oocytes displayed a diffuse pattern of LD distribution, whereas at anestrus and luteal phase oocytes showed LD mainly in a peripheral/ perinuclear LD distribution. A significantly higher intensity of LD has been recorded in the oocytes > 120 µm compared to those of smaller size (110 ‐ 120 µm) at all stages of the estrous cycle. At follicular phase, oocytes > 120 µm displayed LD intensity similar to that of oocytes > 120 µm at luteal phase and higher compared to the oocytes of the other groups.